Towards an Understanding of What it Might Mean to Research Spiritually - Cheryl Hunt; Linden West (Adult Education Research Conference, 2007)
This paper reports on a two-year funded seminar series in the UK. This highlighted two distinct ‘locations’ of spirituality and the need to recognise different ‘ways of knowing’ when working in this field. It also raised questions about what it might mean to research spiritually.